Influence of the Trailing Edge Shape on the Aerodynamic Characteristics of an Airfoil at Low Re Number Using RANS. Issue 1 (July 2020) - Perrin, R.; Rattanasiri, P.; Lamballais, E.; Yooyen, S.
Abstract: Recent studies have demonstrated that periodic spanwise modifications of the trailing edge (henceforth TE) of an airfoil can significantly reduce the noise produced. It has previously been observed that it can also increase its aerodynamic performances. This study aims to analyse the effects of such modifications on the aerodynamic performances of a profile by numerical simulation, with a particular emphasis on low Re numbers typical of Unmanned Aerial Vehicles (henceforth UAV), Micro Aerial Vehicle (MAV), and/or small wind turbines. In the range of Re numbers considered here, the flow presents laminar separation eventually followed by transition and reattachment (depending on Re, Angle of Attack and Free Stream Turbulence). Data for this study were collected using the RANS approach since it is considered standard to use in the industry, and its computational cost is acceptable. By employing this approach, I attempt to illuminate the ability of the proposed transition models and to predict the characteristics of the flow for such geometries with modified TE (see Ge, 2014; Menter, 2015; Kubacki, 2016). This methodological approach taken in this study consists of a baseline NACA0012 profile and a modified TE (blunt TE, and serrated TE). This study also uses simulations that involve the utilisation of Code Saturne (open source 2 nd order finite volume), and the influence of the FST, AoA, and Re on the aerodynamics performances. The results obtained from this study are compared with reference results from the literature. Besides, the development of salt incubator is using the waste heat recovery from the salt boiling process, which is the most beneficial use of heat in the combustion of fuel.